2015
DOI: 10.1021/acsami.5b02641
|View full text |Cite
|
Sign up to set email alerts
|

Defect Engineering and Phase Junction Architecture of Wide-Bandgap ZnS for Conflicting Visible Light Activity in Photocatalytic H2 Evolution

Abstract: ZnS is among the superior photocatalysts for H2 evolution, whereas the wide bandgap restricts its performance to only UV region. Herein, defect engineering and phase junction architecture from a controllable phase transformation enable ZnS to achieve the conflicting visible-light-driven activities for H2 evolution. On the basis of first-principle density functional theory calculations, electron spin resonance and photoluminescence results, etc., it is initially proposed that the regulated sulfur vacancies in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 203 publications
(99 citation statements)
references
References 69 publications
3
96
0
Order By: Relevance
“…UV-Vis diffuse reflectance spectroscopy (DRS) is measured by a Carry 500 UV-Vis spectrophotometer, during which BaSO 4 is served as the background. The photoelectrochemical measurement is similar to previous report [21] . The …”
Section: Materials Characterizationsupporting
confidence: 88%
See 1 more Smart Citation
“…UV-Vis diffuse reflectance spectroscopy (DRS) is measured by a Carry 500 UV-Vis spectrophotometer, during which BaSO 4 is served as the background. The photoelectrochemical measurement is similar to previous report [21] . The …”
Section: Materials Characterizationsupporting
confidence: 88%
“…Fortunately, some previous studies have proved that introducing electron mediators (including Au [21][22][23] , Ag [16,24,25] , reduced graphene oxide [26] and so on) at the interface between PS Ⅰ and PS Ⅱ could reduce the transmission impedance of electrons and improve electron transfer rate across the interface, in which electron mediators act as a transfer channel for carriers. Regrettably, because free electron and hole are photo-excited simultaneously at the surface of PS Ⅰ or PS Ⅱ, and the isotropic migration of photo-induced electron-hole pairs from the bulk to surface of each semiconductor, opposite charge carriers can accumulate inevitably in the surface and its density will gradually increase, inducing serious surface self-recombination [20] .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Among the photocatalysts, zinc sulde (ZnS) has been studied extensively by several researchers. 13 ZnS is an important II-VI group semiconductor, which can rapidly produce electron-hole pairs by photoexcitation and thus create high negative potentials of the excited electron. The theoretical efficiency of the photo-carrier generation of ZnS is much higher than that of TiO 2 because of a direct band gap.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Furthermore, the wurtzite structures of ZnO, GaN, ZnS and CdSe have received vivid attraction because of their unique noncentrosymmetric structures. [20][21][22][23] Among the wurtzite classes, the noncentrosymmetric ZnS also possess a promising semiconducting property and thus suitable for wide range of applications, for instance, UV nanolasers, 24 micro force active sensors, 22 optoelectronic devices, 25 photocatalysts, 26 ultraviolet-light sensors 27 etc. Recently, Chen et al have reported stress induced white and green light emissions from a ZnS based device generated from bending, stretching and even by writing.…”
Section: Introductionmentioning
confidence: 99%